ANALYTICAL MODEL OF NOISE STABILITY CALCULATION OF SYSTEMS WITH MULTIPOSITIONAL MODULATION AND CODING BY REED-SOLOMON ALGORITHM - E. B. Lipkovich; V. A. Kovshik; A. A. Serchenya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The aim of this article is to create analytical models that estimate the continuity and effectiveness of digital radio communication systems using multipositional types of modulation (CAM-M, PM-M, FM-M, AM-M) and block coding according to the Reed–Solomon algorithm (RS) with hard decoding. In contrast to the well-known approaches to determining the noise immunity of systems that require computation model, new estimating models are presented that do not require knowledge of the spectrum coefficients, computer simulation training methods and graphical construction of interference curves for various types of modulation and coding parameters. The calculated ratios presented in the article include only the main parameters of the code (free distance, codeword length, relative code speed) and of the modulation type (modulation order, squared noise immunity). They make it possible to directly determine the theoretically required values of signalto-noise ratios (SNR) for input devices from given probabilistic errors based on RS signals, as well as to study the energy gain from coding (EGC), accessible and frequency-efficient systems. Based on the proposed rations, the calculations of the main characteristics of the communication channels for various parameters of the RS codes, the reliability of reception, types and orders of modulation are performed. Comparison of the results of calculation of noise immunity and system effectiveness given in the article with known similar characteristics obtained as a result of computer modeling confirms the correctness of the presented analytical models. The error of the constructed noise immunity curves does not exceed 0.1 dB in the operating range of the SNR. The materials presented in this article are original and can be used in the design, calculation and development of terrestrial and satellite systems.